[Image 68] - Smith, Captain Sir William [?ob. 1732] (My University, 1802)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
Grand View of rocks on the coast of county of Antrim near the Giant's Causeway seen as looking the way of the Causey and connected with the foregoing scene drawn by Captain Sir William Smith in 1802.
Keywords: Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Giant's Causeway (Northern Ireland); Antrim (Northern Ireland : County) -- Pictorial works; Landscapes (Representations) 1800-1810